The effect of momentum deposition during fireball evolution on flow anisotropy. (8th November 2016) - Schulc, Martin; Tomášik, Boris
Abstract: The highest LHC energies give rise to the production of many pairs of hard partons which deposit four-momentum into the expanding fireball matter. We argue that it is necessary to include momentum deposition during fireball evolution into 3 + 1 dimensional hydrodynamic simulations of the collision. This influence cannot be accounted for simply by modifying the initial conditions of the simulation. The resulting contribution to flow anisotropy is correlated with the fireball geometry and causes an increase of the elliptic flow in non-central collisions. The results are presented for various scenarios with energy and momentum deposition to clearly demonstrate this effect.